Analisis Faktor – Faktor yang Mempengaruhi Ketahanan Pangan di Kota Langsa - Safuridar Safuridar; Nurlaila Hanum; Anggi Pratiwi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of Income, Poor Population, Education, and Life Expectancy on Food Security in Langsa City, both partially and simultaneously in 2013-2022. This type of research is quantitative with the research location in Langsa City. This research uses time series secondary data obtained from the Langsa City Central Statistics Agency (BPS). This research uses data processing techniques using multiple linear regression analysis methods through the Eviews 10 program. The results of this research explain that partially the Poor Population has a positive and insignificant effect on Food Security and Life Expectancy has a negative and significant effect on food security in Langsa City. Education has a positive and significant effect on Food Security and Income has a negative and significant effect on Food Security in Langsa City. Meanwhile, simultaneously Income, Poor Population, Education, and Life Expectancy at Birth have a significant effect on Food Security in Langsa City.